2015
DOI: 10.1111/fcp.12110
|View full text |Cite
|
Sign up to set email alerts
|

Zinc: indications in brain disorders

Abstract: Zinc is the authoritative metal which is present in our body, and reactive zinc metal is crucial for neuronal signaling and is largely distributed within presynaptic vesicles. Zinc also plays an important role in synaptic function. At cellular level, zinc is a modulator of synaptic activity and neuronal plasticity in both development and adulthood. Different importers and transporters are involved in zinc homeostasis. ZnT-3 is a main transporter involved in zinc homeostasis in the brain. It has been found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 175 publications
(230 reference statements)
1
67
0
2
Order By: Relevance
“…Zinc is known to modulate synaptic activity and neuronal plasticity which are directly related to cognitive function [5, 44, 45]. Studies on zinc intake and cognitive function in humans have mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc is known to modulate synaptic activity and neuronal plasticity which are directly related to cognitive function [5, 44, 45]. Studies on zinc intake and cognitive function in humans have mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…It has been generally observed that also the level of zinc transporters (ZnT3, ZIP 1, and 6 as well as ZnT1, 4, and 6) undergo various age-related changes in the brain, and in AD patients (Prakash et al, 2015). Indeed, treatment of ZnT3 KO mice with clioquinol has been found to restore the hippocampal zinc levels and up-regulated key proteins particularly relevant for cognition functions (e.g., presynaptic SNAP-25 and synaptophysin, post-synaptic spinophilin and PSD-95, cell supporting pro-BDNF and DCX, glutamate receptors AMPAR, and NMDAR2a/2b).…”
Section: Discussionmentioning
confidence: 99%
“…Zinc is also tightly regulated in the brain, with higher levels in the amygdala, hippocampus and cortex, predominantly located within glutamatergic neurons known as “zinc enriched neurons” (ZEN) (Nowak et al, 2003b; Prakash et al, 2015). About 15% of all zinc in the CNS is in vesicular form within ZENs (Nowak, 2001).…”
Section: Zinc Homeostasis and Regulationmentioning
confidence: 99%
“…Its general actions are well reviewed, as briefly described in this paper and several excellent reviews (Marger et al, 2014; Nowak, 2015; Prakash et al, 2015), but a role for zinc homeostasis with respect to clinical depression and psychosis is not well appreciated by psychiatrists. Zinc is the second most abundant divalent cation after calcium and is a component in hundreds of enzymes and proteins.…”
Section: Introductionmentioning
confidence: 96%